Effectiveness of educational intervention in raising knowledge regarding breast cancer among female nurses - Muhmooda Abdul Razzaque; Shehla Naeem Zafar; Amjad Ali; Sabir Hussain; Sajida Qureshi (Journal of the Pakistan Medical Association, 2021)
Objective: Objective of this study was to assess the effect of nursing educational session on nurse’s knowledge level related to breast cancer. Methods: Single pretest and posttest quasi experimental study was conducted among 131 enrolled participants in two tertiary care hospitals of Karachi after signed consent. Study was held between the period of January 2018 to July 2018 and after approval of Institutional reviews Board of Dow University of Health Sciences Karachi. Questionnaire of Comprehensive Breast Cancer Knowledge Test (CBCKT) was used to collect data. Results: Majority of the participants were General Nursing Diploma holder i.e. 53 (40.5%). 92 (70.2%) were married, 108 (82.4%) had no history of BC and 47 (35.9%) had 1-4 years of working experience. Statistically significant difference was observed between pre-test score and post-test score in all the three components of knowledge of facts, risk factors and causation and myths of BC( p-value<0.05). Conclusion: The findings of this study conclude that nursing educational session has increased nurses’ knowledge related to BC. Continuous...